Effects of Post-natal Dietary Milk Fat Globule Membrane Polar Lipid Supplementation on Motor Skills, Anxiety, and Long-Term Memory in Adulthood - Sultan, Sébastien; Hauser, Jonas; Oliveira, Manuel; Rytz, Andreas; Preitner, Nicolas; Schneider, Nora (Frontiers in Nutrition, 2021)
Early life nutrition critically impacts postnatal brain maturation and cognitive development. Postnatal dietary deficits in specific nutrients, such as lipids, minerals or vitamins are associated with brain maturation and cognitive impairments. Specifically, polar lipids (PL), such as sphingolipids and phospholipids, are important cellular membrane building blocks and are critical for brain connectivity due to their role in neurite outgrowth, synaptic formation, and myelination. In this preclinical study, we assessed the effects of a chronic supplementation with a source of PL extracted from an alpha-lactalbumin enriched whey protein containing 10% lipids from early life (postnatal day (PND) 7) to adulthood (PND 72) on adult motor skills, anxiety, and long-term memory. The motor skills were assessed using open field and rotarod test. Anxiety was assessed using elevated plus maze (EPM). Long-term object and spatial memory were assessed using novel object recognition (NOR) and Morris water maze (MWM). Our results suggest that chronic PL supplementation improved measures of spatial long-term memory accuracy and cognitive flexibility in the Morris water maze in adulthood, with no change in general mobility, anxiety and exploratory behavior. Our results indicate memory specific functional benefits of long-term dietary PL during postnatal brain development.